2016
DOI: 10.1111/pbr.12407
|View full text |Cite
|
Sign up to set email alerts
|

Identification of quantitative trait loci controlling soybean seed weight in recombinant inbred lines derived from PI 483463 (Glycine soja) × ‘Hutcheson’ (G. max)

Abstract: The objective of this study was to identify quantitative trait loci (QTLs) controlling 100‐seed weight in soybean using 188 recombinant inbred lines (RIL) derived from a cross of PI 483463 and ‘Hutcheson’. The parents and RILs were grown for 4 years (2010–2013), and mature, dry seeds were used for 100‐seed weight measurement. The variance components of genotype (a), environment (e) and a × e interactions for seed weight were highly significant. The QTL analysis identified 14 QTLs explaining 3.83–12.23% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…The descriptive statistical parameters and the frequency distribution analysis of the F 5:6 lines (2 replications) was conducted as mentioned in Kulkarni et al [27]. Analysis of variance (ANOVA) and least significant difference (LSD) analysis was conducted using the general linear model (GLM) in the SAS software program [28] to identify the level of significant difference in the fatty acid concentration in F 5:6 lines.…”
Section: Discussionmentioning
confidence: 99%
“…The descriptive statistical parameters and the frequency distribution analysis of the F 5:6 lines (2 replications) was conducted as mentioned in Kulkarni et al [27]. Analysis of variance (ANOVA) and least significant difference (LSD) analysis was conducted using the general linear model (GLM) in the SAS software program [28] to identify the level of significant difference in the fatty acid concentration in F 5:6 lines.…”
Section: Discussionmentioning
confidence: 99%
“…The study utilized a cross of two cultivated soybeans differing in many traits, including root and shoot traits. However, wild soybeans ( Glycine soja ) have also been shown to possess alleles that can contribute positively to different agronomically important traits in cultivated soybean ( Ha et al, 2013 , 2014 ; Kulkarni et al, 2016 , 2017a ; Patil et al, 2016 ). Lee et al (2014) observed that some of the RILs from an interspecific cross of PI 483463 (a wild soybean accession, with thinner main stems and branches and good forage yield) and “Hutcheson” had higher feeding value than cultivated soybeans, which suggested that the wild soybean PI 483463 may have favorable alleles that could be utilized to improve forage traits.…”
Section: Genetic Dissection Of Forage Traits In Legumesmentioning
confidence: 99%
“…Recent advances in molecular marker technology have facilitated allele mining and gene discovery to aid in the genetic dissection of key traits (Niu et al 2013;Asekova et al 2016b;Kulkarni et al 2016;Kulkarni et al 2017). Maturity is one such trait that has substantial significance in the development of cultivars suitable for the environmental conditions in Kazakhstan.…”
Section: Poor Genetic and Molecular Resourcesmentioning
confidence: 99%